(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2025)
Campylobacter, one of the four key causes of diarrheal diseases of humans, is a zoonotic bacterial pathogen commonly found in cattle, sheep, goats and poultry. As the number of crossbred cattle steadily increases in Bangladesh through intensified livestock production to fulfill the demand of animal-source protein, the risk of pathogenic Campylobacter transmission is likely to increase in humans and animals including the farm environment. The objective of this study was to confirm the risk pathways and estimate the likelihood of entry and exposure risks of Campylobacter for cattle in the farm holdings. Following OIE risk analysis guidelines and tools, we assessed the risk level of each pathway using secondary and field observation data used in expert opinion elicitation process to formulate and confirm the risk level and their combined risk. The probable risk nodes were combined to obtain the total risk level for each specific transmission pathway using the template adapted by Zepeda-Sein based upon expert opinions. The evaluations revealed that the risk of the entry and exposure of Campylobacter is medium with medium levels of uncertainty. Moreover, the consequence pathways showed high risk with low level of uncertainty. Finally, the overall risk for transmission was evaluated as medium with medium level of uncertainty. This study suggests that there is a significant risk of Campylobacter transmission which may spread in humans, animals and successfully maintain in the farm environments. Good animal husbandry practices along with personal hygiene and sanitation practices of animal attendants including their family members are needed to minimize the risk of Campylobacter transmission from farmed cattle to humans. The findings of this study could be useful for framing functional risk reduction measures at the low-resource settings using One Health approach considering human, animal and environmental health perspectives. Asian Australas. J. Biosci. Biotechnol. 2025, 10(1), 6-21